Evidence for the efficacy of pre-harvest agricultural practices in mitigating food-safety risks to fresh produce in North America - Devarajan, Naresh; Weller, Daniel L.; Jones, Matthew; Adell, Aiko D.; Adhikari, Achyut; Allende, Ana; Arnold, Nicole L.; Baur, Patrick; Beno, Sarah M.; Clements, Donna; Olimpi, Elissa M.; Critzer, Faith; et al. (Frontiers in Sustainable Food Systems, 2023)
Consumption of contaminated produce remains a leading cause of foodborne illness. Increasingly, growers are altering agricultural practices and farm environments to manage food-safety hazards, but these changes often result in substantial economic, social, and environmental costs. Here, we present a comprehensive evidence synthesis evaluating the efficacy of soil, non-crop vegetation, animal, landscape, and irrigation water management strategies aimed at reducing the produce-safety risk in North America. Briefly, we systematically summarized findings from 78 peer-reviewed papers on the effect of 21 management practices on the prevalence, abundance, or survival of four foodborne pathogens (i.e., E. coli, Salmonella spp., Listeria spp., and Campylobacter spp.), resulting in 113 summaries. We then organized a 30-member expert panel, who used these summaries to evaluate the impact of each practice on food-safety outcomes. While more than half of the practices were too understudied to confidently evaluate their impact on food safety, the panel did identify several practices that were associated with reduced preharvest food-safety risks, including not using raw manure, separating crop and livestock production, and choosing low-risk irrigation sources. The panel also identified practices that appear ineffective at reducing food-safety risks, such as the removal of non-crop vegetation. Overall, these findings provide insights into the food-safety impacts of agricultural and land management practices that growers, auditors, and extension personnel can use to co-manage produce preharvest environments for food safety and other aims.